Der Kindergarten als Arbeitsplatz für Frauen und Männer Eine Herausforderung für die Geschlechterpolitik - Smidt, Wilfried (innsbruck university press, 2015)
"For many decades, there have been numerous grants to pave the way for women into technical careers and higher positions. The ""glass door"" could thereby break in many areas. On the other hand, the proportion of men in educational professions is steadily decreasing (elementary school about 8%) or traditionally very low (kindergarten 1%). In the past, this challenge has received too little attention from gender policy. That should change."